“ENHANCEMENT OF OPTICAL AND STRUCTURAL PROPERTIES OF SRTIO₃ PEROVSKITE USING NATURAL STABILIZERS” (Universal International Scientific Journal, 2026)
.In this study, the synthesis of SrTiO₃ perovskite material via the sol–gel method in aDMSO medium and the influence of citric acid and yetmak plant extract used as stabilizers on itsoptical properties were investigated. The obtained samples were analyzed using photoluminescence(PL) spectroscopy. The PL spectra exhibited several emission maxima in the 400–1500 nm range. Astrong emission band observed in the 550–600 nm region indicates the presence of defect statesassociated with oxygen vacancies and Ti³⁺ centers in the SrTiO₃ crystal lattice. The emission at higherwavelengths suggests the formation of deep energy levels and surface states. The results confirm thatthe use of citric acid and plant extract during synthesis increases the defect concentration in SrTiO₃and significantly affects its optical activity.
Keywords: SrTiO₃; perovskite; sol–gel method